COPING MECHANISM OF CAREER WOMEN WITH BREAST CANCER - Rosnani Rosnani (Universitas Airlangga, 2017)
Introduction: Patients with cancer may experience psychological disorders such as depression, anxiety, anger, helplessness, and unappreciated, so in certain situations require defense mechanisms (coping mechanism) to oppose or resist feelings of anxiety, fear or stress that haunt her. The aim of this study was to know the coping mechanism of career women with breast cancer reviewed by phenomenology in Palembang 2016. Method: Type of this study was a qualitative study with a phenomenological approach. Total samples were 8 participants with inclusion criteria: career women, productive age range, health physic and physiologic. Independent variable was a coping mechanism, and the dependent variable was breast cancer. The instrument used the voice recorder, and interview guides. Data analyze used verbatim transcript with credibility, dependability, and confirmability. Result: The results showed that working women who have breast cancer have a coping strategy that is adjusted to the psychological condition and physical reactions of the therapy in progress. Psychologically, the coping mechanism is in the form of rejecting, drawing closer to Allah SWT, seeking the opinion of other health workers, discussing conditions with spouse and family, seeking alternative treatment and asking for doctor's direction. The coping mechanism of the body's reaction to therapy is done by taking medicine according to the rules and remember Allah SWT. Conclusions: Need the support of the coping mechanism in patients with breast cancer and nursing care approach with the pattern of coping mechanisms with the involvement of the family.